Diseño de un sistema de acceso remoto, para la verificación y control de las condiciones en el ambiente que presentan los medidores inteligentes de alta demanda. - Muñoz-Chacón, José Antonio (Instituto Tecnológico de Costa Rica, 2012)
This project is located in the area of quality measurement and aims to contribute to the maintenance and security which are peak meters used by the ICE for billing. Measurement is usually surrounded by a number of factors interrupting normal operation. Such are the temperature, moisture, removal of steps and wrong handling of the meter; which makes the process of billing and operation. That is why there is a need to design a remote access system to verify the measurement and condition to facilitate interrogation Storage space meter and Information. Currently there have been advances in remote access to meters peak demand for the interrogation of the same, so This project will be an adaption that can be traced at real-time temperature and humidity conditions in which the measurement is the state phase and the forced opening of the meter.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2012.
Keywords: Calidad; Medición; Electricidad; Servicio al cliente; Seguridad; Comunicación inalámbrica